Associated Petroleum Gas: Problems, Prospects, Ways to Increase Its Effective Use - BURENINA, Irina; EVTUSHENKO, Evgenii; KOTOV, Dmitry; BATTALOVA, Alena; MUKHAMETYANOVA, Guzel; GAMILOVA, Dilyara (Journal of Environmental Management and Tourism, 2018)
The purpose of the study is to analyze the efficiency of using associated petroleum gas (APG) and to identify the main problems, prospects and ways to increase the efficiency of its use. The article presents the results of studying the current state policy and national interests in the field of its rational use. The authors carried out an analysis of the current state of the oil and gas market at the international and regional level, as a result of which the main spectrum of problems of APG effective use was identified. A scheme was proposed which regulates the interaction between the APG market participants and is aimed at increasing the level of APG beneficial use in Russia. The authors’ research will make it possible to determine that the most significant factors that ensure a high level of APG flaring in Russia are as follows: the shortage of APG processing capacity, the restriction of oil companies’ access to the Unified Gas Supply System, the gaps in the current legal and regulatory framework, the absence of a single mechanism for the selection of projects on utilizing APG in a particular field/group of fields, as well as pricing in the oil and gas market. The findings are of practical value for scholars in the field of technology management, and for large industrial complexes.